2018
DOI: 10.1371/journal.pone.0203048
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR and MALDI-TOF MS as metabolomic quality control tests to classify platelet derived medium additives for GMP compliant cell expansion procedures

Abstract: IntroductionEx vivo cell expansion under Good Manufacturing Practice (GMP) guidelines can be performed using medium additives containing human growth factors from platelets. These products can differently affect proliferation of adipose mesenchymal stromal stem cells (ASC). Qualification of medium additive performance is required for validation under GMP regulations: assessment of growth factor concentrations is not sufficient to predict the biological activity of the product batch. Proton nuclear magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We demonstrated that to obtain stable SRGF batches, that equally stimulate MSC proliferation rate, at least 16 different SRGF products derived from single donors must be mixed together[ 69 ]: To achieve this aim, we adopted a predictive mathematical approach, followed by “wet biology” validation. In order to identify, in compliance with GMP requirements, a reliable and comprehensive quality control assay for SRGF, we manufactured from platelet concentrates several medium additive types differently promoting ASC growth rate[ 70 ]. Interestingly, while integrative analysis of growth factor concentration changes was shown to be insufficiently sensitive, 1 H-NMR and MALDI-TOF MS could clearly identify differences between product isoforms.…”
Section: Msc Expansion For Clinical Usementioning
confidence: 99%
“…We demonstrated that to obtain stable SRGF batches, that equally stimulate MSC proliferation rate, at least 16 different SRGF products derived from single donors must be mixed together[ 69 ]: To achieve this aim, we adopted a predictive mathematical approach, followed by “wet biology” validation. In order to identify, in compliance with GMP requirements, a reliable and comprehensive quality control assay for SRGF, we manufactured from platelet concentrates several medium additive types differently promoting ASC growth rate[ 70 ]. Interestingly, while integrative analysis of growth factor concentration changes was shown to be insufficiently sensitive, 1 H-NMR and MALDI-TOF MS could clearly identify differences between product isoforms.…”
Section: Msc Expansion For Clinical Usementioning
confidence: 99%
“…75 1 H NMR was recently used by Agostini et al to characterize and predict the quality of platelet-derived media supplements for industrial cell manufacturing, leveraging the ease of sample preparation and throughput of media analysis by NMR. 76 Continuous flow NMR techniques for monitoring mammalian cell culture systems have existed for decades 35…”
mentioning
confidence: 99%